The Think-Pair-Share Approach in Learning Indonesian Language for Semester 1 Students of English Education Program - Baan, Anastasia (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to describe (a) the ability of lecturers to manage the Think-Pair-Share approach (b) Student activities in learning activities using the Think-Pair-Share Approach (c) student learning outcomes. The sample for this study was determined using total sampling, namely all semester 1 students in class A of the UKI Toraja English Education Study Program, a total of 25 students. The instruments used to collect data were (1) observation sheets on the lecturer's ability to manage learning, by means of observers observing the lecturer's ability to manage the Think-Pair-Share approach, then giving an assessment of the aspects on the observation sheet, (2) activities students were also observed using observation sheets, and (3) student learning outcomes were obtained through learning achievement tests. After the data is collected, then the data is analyzed using descriptive statistics. The results of the research analysis show that: (a) the ability of lecturers to manage learning is categorized as good, with an average score of 3.91 (b) the Think-Pair-Share approach is active, this can be seen from the average percentage of students while being observed three times. meeting times, namely 63.75 and (c) by managing the Think-Pair-Share approach can improve student learning completeness. This can be seen from the results of the initial test of 25 students, none of whom completed their study results with an average of 12.865, in the final test of completeness results student learning increased 69.56 from 25 students. Overall, the findings suggest that the TPS approach is beneficial for both lecturers and students in enhancing English language learning for semester 1 students in an English Education Program. This study highlights the importance of lecturers' effective management of the TPS approach and the positive impact on student activities and learning outcomes in English language classes.